Integrating transcriptomic and metabolomic analysis of hormone pathways in Acer rubrum during developmental leaf senescence - Zhu, Chen (BMC Plant Biol, 2020)
BACKGROUND: To fully elucidate the roles and mechanisms of plant hormones in leaf senescence, we adopted an integrated analysis of both non-senescing and senescing leaves from red maple with transcriptome and metabolome data. RESULTS: Transcription and metabolite profiles were generated through a combination of deep sequencing, third-generation sequencing data analysis, and ultrahigh-performance liquid chromatograph Q extractive mass spectrometry (UHPLC-QE-MS), respectively. We investigated the accumulation of compounds and the expression of biosynthesis and signaling genes for eight hormones. The results revealed that ethylene and abscisic acid concentrations increased during the leaf senescence process, while the contents of cytokinin, auxin, jasmonic acid, and salicylic acid continued to decrease. Correlation tests between the hormone content and transcriptional changes were analyzed, and in six pathways, genes closely linked with leaf senescence were identified. CONCLUSIONS: These results will enrich our understanding of the mechanisms of plant hormones that regulate leaf senescence in red maple, while establishing a foundation for the genetic modification of Acer in the future.